Is FDG uniformly distributed throughout the skeleton in females - DEDE, FUAT; ÖNEŞ, TUNÇ; ÖZGÜVEN, SALİH; ERDİL, TANJU YUSUF; TUROĞLU, HALİL TURGUT (My University, 2011)
Introduction: FDG PET/CT has been extensively used for imaging primary or metastatic bone lesions. Although the relationship between SUVmax value and benign and malignant bone lesions were investigated in previous studies, the differential physiologic bio-distribution of FDG throughout the skeleton was not analysed before. The aim of this study was to investigate whether FDG was uniformly distributed throughout the skeleton in female patients. Methods: A total of 100 female cancer patients, who were referred to our clinic for initial staging with FDG PET were included in this retrospective study. None of the patients had received prior treatment that directly affected bone marrow (chemotherapy, radiotherapy or colony stimulating factors) and the patients had no history of anaemia. The patients who had bone metastases were excluded from the study. The maximum standard uptake value (SUVmax) of the 24 different locations (the heads and proximal diaphysis of the bilateral upper and lower extremities, rib (10th rib) sternum (manibrium and corpus), vertebral column (C3, C5, T3, T7, L1, L3) and bilateral pelvic bones (sacrum and bilateral anterior and posterior parts of the iliac bones and acetabulum) were obtained and all the values were compared to each other. Results: Although FDG uptake in the skeleton was not uniform (p<0.05), the mean SUVmax was 2.05 (SD: 0.39 and 95% Conf. limit: 1.98 – 2.13). While the highest FDG uptake was seen in L3 vertebra (mean SUVmax: 3.009), the least glucose metabolism was observed in the 10th rib (mean SUVmax: 1.432). The SUVmax of the bilateral heads of the upper and lower extremity were significantly higher than the neighbouring diaphysis (p < 0.05). The SUVmax of the manibrium of the sternum was significantly higher than the corpus (p < 0.05). For pelvic bones, while the highest FDG uptakes were detected in the sacrum (mean SUVmax :2.73), the least FDG uptakes were seen in anterior iliac bones (SUVmax: 1.82), (p < 0.05). For vertebral column FDG uptakes were also non-uniform and the SUVmax gradually increases from cervical to the lumber part (C3-mean SUV max: 2.28, L3-meanSUVmax: 3.0), (p < 0.05). On the other hand, mean skeletal SUVmax was decreased by age (r: -0.20, p<0.05). Conclusion: The FDG was not uniformly distributed throughout the skeleton in female patients. It had a tendency to increase from appendicular to the axial skeleton and from upper to lower regions in the vertebral column which may be related to the normal distribution of the red bone marrow. Additionally, through age, glycolytic metabolism of the whole skeleton showed a gradual decrease.